God's Rascal : J. Frank Norris and the Beginnings of Southern Fundamentalism - Hankins, Barry, 1956- (Book collections on Project MUSE., 2010)
Colorful and outrageous, influential yet despicable, J. Frank Norris was a preacher, newspaper publisher, political activist, and all-around subject of controversy. One of the most despised men in traditional Southern Baptist circles, he was also the man most responsible for bringing hard-edged fundamentalism to the South. Barry Hankins traces Norris, the ""Texas Cyclone, "" from his boyhood in small-town Texas to his death in 1952. Despite scandals, Norris was a man of considerable public influence who traveled the owrkd, corresponded with congressmen, and attended president's Hoover's inagura.